Legal Reform Regarding the Authority of Public Prosecutors in Implementing Diversion Programs for Children in Conflict with the Law - Imma Purnama Sari; Diana Haiti; Nurunnisa Nurunnisa (International Journal of Sociology and Law, 2025)
The Indonesian Law No. 11 of 2012 concerning the Juvenile Criminal Justice Sistem (SPPA Law) established Diversion and Restorative Justice as core pillars for handling Children in Conflict with the Law (CICL). The Public Prosecutor (JPU) plays a mandatory role in attempting Diversion, as stated in Article 7(1) of the SPPA Law. However, the implementation of Diversion is hindered by judicial limitations, such as restrictions on crimes with a prison sentence of less than seven years and the lack of specific government regulations (PP). These barriers often deny children the opportunity for Diversion, exposing them to the formal justice process and stigmatization. This study analyzes the challenges within the JPU’s authority regarding Diversion and proposes legal reforms to strengthen their role. Using normative legal research and a conceptual approach, the study examines primary and secondary legal materials and suggests the implementation of a Digital Decision Support Sistem (DSS) to guide prosecutorial discretion. The findings reveal that restrictive penal criteria and the absence of a review mechanism for rejected Diversion cases undermine Restorative Justice efforts. The paper argues that legal reforms are necessary to revise penal limitations, develop a detailed regulatory framework, and implement an integrated information sistem to support rehabilitation programs, ensuring the best interests of children and reducing reoffending.